General Method for the Synthesis of 1, 4‐Disubstituted 5‐Halo‐1, 2, 3‐triazoles. Issue 35 (19th September 2017) - Gribanov, Pavel S.; Topchiy, Maxim A.; Karsakova, Iuliia V.; Chesnokov, Gleb A.; Smirnov, Alexander Yu.; Minaeva, Lidiya I.; Asachenko, Andrey F.; Nechaev, Mikhail S.
Abstract : A general method for the synthesis of 1, 4‐disubstituted 5‐halo‐1, 2, 3‐triazoles has been developed. The one‐pot two‐step process consists of a CuAAC reaction of a copper(I) acetylide with an organic azide catalyzed by ( a NHC)CuCl, followed by halogenation with N ‐chlorosuccinimide, N ‐bromosuccinimide, or I2 . Abstract : A high‐yielding, robust, easily scalable one‐pot two‐step approach to the synthesis of 1, 4‐disubstituted 5‐halo‐1, 2, 3‐triazoles is reported.